Metacognitive-Based Indonesian Language Learning Using Animated Videos as a Strategy to Improve Reading Literacy - Misrini; I Dewa Ketut Artha Saputra; I Made Adi Wicaksana; Nailis Sa'adah; I Nyoman Sudiana; Ida Bagus Putra Yasa (International Journal of Language and Literature, 2025)
Reading literacy is a fundamental competency that students must have. However, in conventional learning practices, reading literacy still faces obstacles such as a lack of motivation and limited students' in-depth understanding of reading texts. This study aims to analyze the effectiveness of Indonesian language learning, using metacognitive learning assisted by animated videos, in improving the reading literacy of fifth-grade elementary school students. This study uses a quantitative approach and a simple experimental design (a one-shot case study). This study involved 26 fifth-grade students. The data collection method uses a test. The research instrument is a reading literacy test. The data obtained are analyzed descriptively using SPSS version 25.0. The results show that the average reading literacy score was 83.57, with 89.29% of students scoring above the Minimum Completion Criteria (KKM) of 75. Animated video media has been shown to increase students' motivation and active involvement in the learning process, as well as support the development of students' metacognitive abilities in reading. This study recommends implementing metacognitive learning through animated videos as an innovative strategy to improve reading literacy among elementary school students. The implications of this research can be a reference for curriculum development and learning practices in elementary schools, especially in the context of teaching Indonesian.